Electrochemically stable artificial muscles from directly spun carbon nanotube fibers - Park, Chae-Lin; Goh, Byeonghwa; Oh, Seongjae; Lee, Jae Won; Seo, Won Yong; Song, Young-Chul; Kim, Hyun; Ko, Seung Hwan; Choi, Changsoon; Kim, Seon Jeong; Han, Mingook; Lim, Taewan; et al. (Pergamon Press Ltd., 2026)
Carbon nanotube fibers (CNTFs) are considered promising electrochemically powered actuators for wearable technologies and soft robotics due to their high actuation stroke and low-voltage operation for their exceptional mechanical and electrical properties. Direct-spun CNTFs offer a scalable alternative to forest-spun CNTFs, but their rapid fabrication results in poor internal alignment and low packing density, leading to reduced mechanical reliability under cyclic actuation. In this study, we present an electrochemically stable twist-based artificial muscle utilizing direct-spun CNTFs, in which the intrinsic limitations are overcome through polymer reinforcement. Using a graded infiltration strategy, poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP) was infiltrated into the CNTFs, forming a hierarchical polymer-reinforcement distribution across the sheath-to-core interface. This architecture enables robust structural integration with the bias angle variation across the cross-section of the host muscles. As a result, the compositional and structural design of the hybrid muscles leads to a 38 % increase in mechanical strength and a 14.6 % improvement in electrochemical cycling stability. Furthermore, molecular dynamics simulations revealed the suppression of electrochemical creep at the molecular level, confirming that the polymer matrix reduces interfacial slippage and stress concentration within CNT bundles. This molecular-level insight into creep suppression has not been previously reported for CNTF-based artificial muscles. Our findings establish a viable pathway toward scalable and robust artificial actuators suitable for long-term operation.